Improvement of Indigofera zollingeriana Production and Methionine Content through Inoculation of Nitrogen-Fixing Bacteria - P. S. Hutapea; L. Abdullah; P. D. M. H. Karti; I. Anas (Tropical Animal Science Journal, 2018)
Indigofera zollingeriana is a tremendous potential as a forage plant due to its high protein content. This experiment was conducted to increase production and nutrient quality of I. zollingeriana biomass, especially methionine content through inoculation of nitrogen fixing bacteria. Nine isolates obtained from nodule of I. zollingeriana were screened for 37 days in greenhouse, resulting in three desirable isolates. These three selected isolates at density of 105 cfu/mL and 107 cfu/mL were inoculated as much as 1 mL per seedling. Uninoculated plants were also grown as control treatment, i.e., positive (+ 0.05% KNO3 (w/v)) and negative. The experiment was laid out in a completely randomized design with four replicates and carried out for three months. Plant biomass was analyzed for amino acid and other nutrient contents. Moreover, nodulation activity was also observed by counting and weighting the nodules. The results showed that Bradyrhizobium sp. P8 828, Bradyrhizobium sp. PZS_A08, and Roseomonas sp. CMS4Y-2-2 significantly increased shoot production. Subsequent experiment showed that plant inoculation with Bradyrhizobium sp. PZS_A08 at 105 cfu/mL significantly increased dry matter content. Inoculation with Bradyrhizobium sp. PZS_A08 and Roseomonas sp. CMS4Y-2-2 at 107 cfu/mL produced higher crude protein contents that were better than the application of nitrogen fertilizer. Inoculation treatment with Bradyrhizobium sp. P8 828 at 105 cfu/mL was the most effective in improving methionine content. It is concluded that production and quality of biomass obtained from inoculation treatments were comparable to the application of inorganic N-fertilizer.